Identification of an allatostatin from the tobacco hornworm Manduca sexta. - Kramer, S J (1991)
A peptide (Manduca sexta allatostatin) that strongly inhibits juvenile hormone biosynthesis in vitro by the corpora allata from fifth-stadium larvae and adult females has been purified from extracts of heads of pharate adult M. sexta by a nine-step purification procedure. The primary structure of this 15-residue peptide has been determined: pGlu-Val-Arg-Phe-Arg-Gln-Cys- Tyr-Phe-Asn-Pro-Ile-Ser-Cys-Phe-OH, where pGlu is pyroglutamate). To our knowledge, this neuro-hormone has no sequence similarity with any known neuropeptide from other organisms. The synthetic free acid and amide forms showed in vitro activity indistinguishable from that of native M. sexta allatostatin. The ED50 of synthetic M. sexta allatostatin on early fifth stadium larval corpora allata in vitro was approximately 2 nM. This inhibition was reversible. In a cross-species study, M. sexta allatostatin also inhibited the corpora allata of adult female Heliothis virescens but had no effect on the activity of corpora allata of adult females of the beetle Tenebrio molitor, the grasshopper Melanoplus sanguinipes, or the cockroach Periplaneta americana.